Accents in Speech Recognition through the Lens of a World Englishes Evaluation Set - Miguel Del Río; Corey Miller; Ján Profant; Jennifer Drexler-Fox; Quinn Mcnamara; Nishchal Bhandari; Natalie Delworth; Ilya Pirkin; Migüel Jetté; Shipra Chandra; Peter Ha; Ryan Westerman (Research in Language)
Automatic Speech Recognition (ASR) systems generalize poorly on accented speech, creating bias issues for users and providers. The phonetic and linguistic variability of accents present challenges for ASR systems in both data collection and modeling strategies. We present two promising approaches to accented speech recognition— custom vocabulary and multilingual modeling— and highlight key challenges in the space. Among these, lack of a standard benchmark makes research and comparison difficult. We address this with a novel corpus of accented speech: Earnings-22, A 125 file, 119 hour corpus of English-language earnings calls gathered from global companies. We compare commercial models showing variation in performance when taking country of origin into consideration and demonstrate targeted improvements using the methods we introduce.